2018
DOI: 10.1007/s00421-018-4020-y
|View full text |Cite|
|
Sign up to set email alerts
|

Inert gas narcosis in scuba diving, different gases different reactions

Abstract: Purpose Underwater divers face several potential neurological hazards when breathing compressed gas mixtures including nitrogen narcosis which can impact diver's safety. Various human studies have clearly demonstrated brain impairment due to nitrogen narcosis in divers at 4 ATA using critical flicker fusion frequency (CFFF) as a cortical performance indicator. However, recently some authors have proposed a probable adaptive phenomenon during repetitive exposure to high nitrogen pressure in rats, where they fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 38 publications
2
26
1
Order By: Relevance
“…Indeed, shortterm normobaric O 2 (maximum 101 kPa O 2 ) influenced cognitive abilities such as memory, visuospatial and verbal abilities in a positive manner, 28 whilst functional MRI studies have demonstrated that normobaric hyperoxia (30 kPa O 2 ) during verbal or visual tasks increases the activation of brain areas associated with cognitive processing. 29 In divers, an association between changes in response times and changes in CFFF suggest that divers susceptible to IGN may also be susceptible to the effects of elevated PO 2 . 30 Also, even a small reduction in PN 2 , associated with a conservative dive profile, resulted in a modest beneficial effect of EANx28 (28% O 2 -72% N 2 ) on performance that may contribute to diving safety.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, shortterm normobaric O 2 (maximum 101 kPa O 2 ) influenced cognitive abilities such as memory, visuospatial and verbal abilities in a positive manner, 28 whilst functional MRI studies have demonstrated that normobaric hyperoxia (30 kPa O 2 ) during verbal or visual tasks increases the activation of brain areas associated with cognitive processing. 29 In divers, an association between changes in response times and changes in CFFF suggest that divers susceptible to IGN may also be susceptible to the effects of elevated PO 2 . 30 Also, even a small reduction in PN 2 , associated with a conservative dive profile, resulted in a modest beneficial effect of EANx28 (28% O 2 -72% N 2 ) on performance that may contribute to diving safety.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found no indication of increased ROS production that could explain the differences between diving and non-diving rats. It may be worth noting that ventilation with helium has been reported to have an anti-inflammatory effect (Brubakk et al, 2014; Rocco et al, 2019), which may have reduced any side effect of potential O 2 toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…When the subject saw a change in LED light from flicker to fusion, the subject acknowledged it to the investigator (through a sign without leaving sight of the LED) and the test was stopped. This noninvasive test has been validated to measure awareness (Hemelryck et al, 2013; Balestra et al, 2018; Rocco et al, 2019), mental fatigue (Ma et al, 2014), or executive dysfunction (Mewborn et al, 2015). It has already been demonstrated that CFFF could follow the recovery of cognitive function after propofol sedation earlier than psychometric testing (Sharma et al, 2011).…”
Section: Methodsmentioning
confidence: 99%